MODELS OF EVALUATION (MULTIDISCIPLINARY JOURNAL: FUNDAMENTAL RESEARCH SCIENTIFIC JOURNAL, 2025)
This article explores the Kirkpatrick Assessment Model as a comprehensive framework for evaluating training programs and curricula. It outlines the model’s four levels—Reaction, Learning, Behavior, and Results—and discusses how each phase contributes to understanding the effectiveness of training initiatives. The article emphasizes the importance of assessing not only immediate participant feedback but also long-term behavioral changes and organizational outcomes. Practical examples, such as teacher training in technology integration, are provided to illustrate each level. Although the model is sometimes criticized for being overly simplistic, it remains a valuable tool in both educational and professional settings for improving performance and achieving measurable results.